Operasionalisasi Pemikiran Ijtihad Iqbal dalam Bingkai Proposisi Esensialnya Mutahhari - Umi Chaidaroh (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2007)
Islam and social change are two different sides of two different coins. They seem forever separable. But Muslims soon realize that they live within particular social context. This certainly has compelled them to consider how they should deal with Islam vis-a-vis the changing reality of human life which is both fast in its quality and massive in its quantity. This paper tries to explore this issue by referring to the thought of Muhammad Iqbal and Murtad Mutahhari.